Scaling a landfarming treatment of oily sludge using criteria of a batch reactor - Jerônimo, Carlos Enrique de Medeiros; Kitzinger, Wigler Gomes da Costa Martins (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper presents a criterion for sizing systems landfarmings, which takes into account the kinetic model of the degradation of pollutants in oily sludge , levels of speeds involved in chemical reactions and adaptation of the theory of batch reactor for the sizing of the ground be installed infrastructure for treatment , since this subject is considered unprecedented in the literature and technical standards that guide the design models of these systems . The methodology used in the development of this work involved the interpretative analysis of texts and pictures present in scientific articles , books , papers and course completion . As analysis of ABNT NBR 13894 1997 for soil treatment (landfarming) . Kinetic data were obtained and considered for kinetic mathematical adjustments first and second order reactions analyzed. The proposed criterion, using the principles of operation of a batch reactor applied to a system Landfarming presented as an acceptable method and consists in advancing the state of the art design methodologies for safe and efficient for this type of system.